2019
DOI: 10.1097/scs.0000000000005392
|View full text |Cite
|
Sign up to set email alerts
|

Adipogenic Mesenchymal Stem Cells and Hyaluronic Acid as a Cellular Compound for Bone Tissue Engineering

Abstract: This study investigates the applicability of adipose mesenchymal stem cells (mADSCs) and hyaluronic acid (HA) as a cellular compound for bone tissue engineering. A critical bone defect was created on each femur of 25 rats in vivo, receiving the following 5 graft treatments: I-Control-defect; II-HA; III-mADSCs; IV-mADSCsþHA; and V-previously osteoinduced mADSCsþHA. Evaluation using microcomputed tomography, histomorphometry, and RT-PCR analysis was performed 23 days after implantation. Microcomputed tomography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…Results reported here indicated that differentiated ASCs had their growth factors production negatively affected in comparison with undifferentiated ASCs. Corroborating these findings, similar cellular responses were observed when a combination of ASCs and HA-LW was evaluated in bone tissue engineering in vivo [15], where results suggested that the combination of HA-LW and uninduced ASCs favored bone formation in critical defects.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Results reported here indicated that differentiated ASCs had their growth factors production negatively affected in comparison with undifferentiated ASCs. Corroborating these findings, similar cellular responses were observed when a combination of ASCs and HA-LW was evaluated in bone tissue engineering in vivo [15], where results suggested that the combination of HA-LW and uninduced ASCs favored bone formation in critical defects.…”
Section: Discussionsupporting
confidence: 62%
“…Associated with MSCs, one scaffold of particular interest considered applicable in tissue engineering is HA, a hydrogel polymer of natural origin, belonging to the family of glycosaminoglycans (GAGs) and present in the extracellular matrix of living tissues [15]. However, there is still no consensus on the ideal presentation and concentration of HA for application as cell scaffold in tissue engineering, since it might elicit distinct effects on cultured and local cells based on its physicochemical properties, especially molecular weight [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of HA and stem cells has also been investigated in different models of osteogenesis. The applicability of adipose-derived MSCs and HA showed higher means of bone regeneration in rat model of bone defects ( Boeckel et al, 2019 ). The combination of BM-MSCs and HA successfully indicated bone regeneration in rat calvarial defect model ( Kim et al, 2007 ).…”
Section: Therapeutic Applications Of Mscsmentioning
confidence: 99%
“…At present, bone tissue engineering technology provides a good prospect for the reconstruction of personalized and functional bone defects in the repair of jaw defects. However, there are still many deficiencies in biomaterials [4]. e emergence of 3D printing technology provides a new solution [5].…”
Section: Introductionmentioning
confidence: 99%